Cx43 Hemichannels and panx1 Channels Contribute to Ethanol-Induced Astrocyte Dysfunction and Damage - Ortiz-Cisternas, F (BioMed Central Ltd, 2024)
Background: Alcohol, a widely abused drug, significantly diminishes life quality, causing chronic diseases and psychiatric issues, with severe health, societal, and economic repercussions. Previously, we demonstrated that non-voluntary alcohol consumption increases the opening of Cx43 hemichannels and Panx1 channels in astrocytes from adolescent rats. However, whether ethanol directly affects astroglial hemichannels and, if so, how this impacts the function and survival of astrocytes remains to be elucidated. Results: Clinically relevant concentrations of ethanol boost the opening of Cx43 hemichannels and Panx1 channels in mouse cortical astrocytes, resulting in the release of ATP and glutamate. The activation of these large-pore channels is dependent on Toll-like receptor 4, P2X7 receptors, IL-1β and TNF-α signaling, p38 mitogen-activated protein kinase, and inducible nitric oxide (NO) synthase. Notably, the ethanol-induced opening of Cx43 hemichannels and Panx1 channels leads to alterations in cytokine secretion, NO production, gliotransmitter release, and astrocyte reactivity, ultimately impacting survival. Conclusion: Our study reveals a new mechanism by which ethanol impairs astrocyte function, involving the sequential stimulation of inflammatory pathways that further increase the opening of Cx43 hemichannels and Panx1 channels. We hypothesize that targeting astroglial hemichannels could be a promising pharmacological approach to preserve astrocyte function and synaptic plasticity during the progression of various alcohol use disorders. © The Author(s) 2024.